If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r + 5 = 17 + 2r Reorder the terms: 5 + 4r = 17 + 2r Solving 5 + 4r = 17 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. 5 + 4r + -2r = 17 + 2r + -2r Combine like terms: 4r + -2r = 2r 5 + 2r = 17 + 2r + -2r Combine like terms: 2r + -2r = 0 5 + 2r = 17 + 0 5 + 2r = 17 Add '-5' to each side of the equation. 5 + -5 + 2r = 17 + -5 Combine like terms: 5 + -5 = 0 0 + 2r = 17 + -5 2r = 17 + -5 Combine like terms: 17 + -5 = 12 2r = 12 Divide each side by '2'. r = 6 Simplifying r = 6
| x^2+5x-(2k+4)=0 | | F(5)=1-4*5 | | xdy+(x+y)DX=0 | | F(4)=1-4*4 | | -2(3x-4)-55=5x-11(x+1) | | -8(x+7)=-88 | | 1/4y-3=1/7y | | F(3)=1-4*3 | | F(2)=1-4*2 | | 8-k=k-6 | | -12+5p=p+4 | | 20x-(4x-3)=51 | | s(s+4)=192 | | 5-4p=-3p-2 | | 5x-7x+2=x-3+5 | | -4x-8=-14-2x | | 11z-3(z-9)=123# | | -8x+8(1+3x)=-120 | | -5a+4a+16=4-5a | | F(5)=4*5+5 | | 3/2@-8=11 | | 8x-2=3+7x | | 6x+20=137 | | -5(t-3)-7(-3t-8)=15(t+3)-4 | | 13/9=x/18 | | F(4)=4*4+5 | | 2.89=0.86b | | (2x^2-4x)(x-2)=0 | | 26-3w=5 | | -4(z-1)=-5z | | 1/100000000 | | (3x+2y^2)ydx+2(2x+3y^2)xdy=0 |